How Loud Do the Alarm Bells Toll? Execution of 'Article 18 Judgments' of the European Court of Human Rights - Çali, Başak (European Convention on Human Rights Law Review, 2021)
This article investigates whether Article 18 judgments of the European Court of Human Rights, indicating that the state authorities pursued ulterior and illegitimate motives when violating the Convention, receive the seriousness and the urgency that they call for at the execution phase. By way of an analysis of the responses of the Committee of Ministers and states on the receiving end of Article 18 judgments between 2004 and June 2021, this article finds that the collective responsiveness of the Committee of Ministers to Article 18 judgments has increased over time, especially with respect to individual measures required to implement Article 18 judgments. So far, the responsiveness of individual states to their Article 18 judgments does, however, vary significantly, ranging from taking concrete steps to implement the judgments to outright resistance and no response, posing a significant risk to the Convention system's ability to respond to the decay of rule of law.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Article 18 echr; Committee of Ministers; execution of the judgments of the European Court of Human Rights; individual and general remedies